Effects of ozone and particulate matter on airway epithelial barrier structure and function: a review of in vitro and in vivo studies. (16th April 2021) - Smyth, Timothy; Georas, Steve N.
Abstract: The airway epithelium represents a crucial line of defense against the spread of inhaled pathogens. As the epithelium is the first part of the body to be exposed to the inhaled environment, it must act as both a barrier to and sentinel against any inhaled agents. Despite its vital role in limiting the spread of inhaled pathogens, the airway epithelium is also regularly exposed to air pollutants which disrupt its normal function. Here we review the current understanding of the structure and composition of the airway epithelial barrier, as well as the impact of inhaled pollutants, including the reactive gas ozone and particulate matter, on epithelial function. We discuss the current in vitro, rodent model, and human exposure findings surrounding the impact of various inhaled pollutants on epithelial barrier function, mucus production, and mucociliary clearance. Detailed information on how inhaled pollutants impact epithelial structure and function will further our understanding of the adverse health effects of air pollution exposure.